The effect of additive, subtractive, and conventional manufacturing methods on the flexural strength of occlusal splints: an in vitro study - Eyyupoğlu, Suzan Eda; Bilir, Halenur (Brazilian Dental Science, 2026)
Objective: This study evaluated and compared the flexural strength of occlusal splints manufactured using conventional, subtractive, and additive manufacturing methods. Material and Methods: A total of 60 specimens were prepared: 45 rectangular for uniaxial flexural strength (64 × 10 × 3.3 mm) and 15 disc-shaped for biaxial flexural strength (12.5 mm diameter, 1.5 mm thickness). The specimens were divided into 3 groups according to their manufacturing methods: conventional (heat-polymerized resin), subtractive (pre-polymerized resin block), and additive (light-polymerized liquid resin). In the additive group, both uniaxial and biaxial flexural strengths were evaluated. Rectangular specimens were tested using a three-point bending test and disc-shaped specimens were used for a piston-on-three-ball test. All measurements were performed using a universal testing machine. One-way ANOVA, Weibull analysis, and Chi-square tests were used for statistical analyses (α = 0.05). Results: The mean uniaxial flexural strength was 54.33 MPa for the additive group, 132.77 MPa for the conventional group, and 133.71 MPa for the subtractive group. The additive group also demonstrated a mean biaxial strength of 82.01 MPa. There are statistically significant differences among the groups (p < 0.001). Conclusion: Within the limitations of this study, the flexural strength of occlusal splints was influenced by the manufacturing methods. The conventional and subtractive manufacturing methods were prone to have high flexural strength values. Although additive methods showed lower flexural strength, variations in printing and post-curing parameters reported in the literature may improve performance. Further studies under simulated oral conditions are required to evaluate their long-term clinical applicability.KEYWORDSComputer-aided design; Dental materials; Flexural strength; Occlusal splints; Three-dimensional printing.